Appendix to Understanding and Improving Software Build Teams - Phillips, Shaun; Zimmermann, Tom; Bird, Christian (Microsoft Research, 2014)
This technical report contains supplemental information to the paper “Understanding and Improving Software Build Teams”, published in the Proceedings of the 36h International Conference on Software Engineering (ICSE 2014), Hyderabad, India, June 2014. The technical report contains the survey, interview guide, focus group protocolm, and list of codes and categories used for analysis.